Effect of hormonal contraceptives on lipid profile and the risk indices for cardiovascular disease in a Ghanaian community - Asare GA; Santa S; Ngala RA; Asiedu B; Afriyie D; Amoah AGB (Dove Medical Press, 2014)
George A Asare,1 Sheila Santa,1 Robert A Ngala,2 Bernice Asiedu,1 Daniel Afriyie,3 Albert GB Amoah4 1Department of Medical Laboratory Sciences, University of Ghana School of Allied Health Sciences (SAHS), Korle-bu, Ghana; 2Department of Molecular Medicine, School of Medical Sciences, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana; 3Department of Pharmacology, University of Ghana Medical School Korle-bu, Ghana; 4Department of Medicine, University of Ghana Medical School, Korle-bu, Ghana Background: Hormonal contraceptives (HCs) have been shown to alter lipid profile among various population groups with different patterns of dyslipidemia and cardiovascular (CV) risk. The study aimed at determining the lipid profile pattern and CV risk in a Ghanaian cohort. Methods: Purposive random sampling was done. Forty-seven and 19 cases were on oral contraceptives (OCs) and injectable contraceptives (ICs), respectively; five were on subdermal implant. Twenty-four non-users served as controls. Biodemographic and lipid profiles were determined. Total cholesterol (TC), high-density lipoprotein cholesterol (HDLC), low-density lipoprotein cholesterol (LDLC), and very-low-density lipid lipoprotein cholesterol (VLDLC), were determined. Castelli index I and II were calculated. Results: The mean age difference between the HC and control groups was insignificant. However, diastolic blood pressure (BP) differences were significant (P=0.006). The body mass index (BMI) of the OC and IC groups were significantly different from the control group (P=0.003 and P=0.008, respectively). TC levels for the control and case groups were 3.35±0.62 mmol/L and 4.07±0.91 mmol/L, respectively (P=0.002). LDLC levels for the control and case groups were 1.74±0.57 mmol/L and 2.38±0.84 mmol/L, respectively (P=0.003). Castelli index I (TC/HDLC) and II (LDLC/HDLC) were significantly different between the control and OC groups (P=0.026 and P=0.014, respectively). Spearman’s rho correlation showed significant influence of HC use on TG (P=0.026), TC (P=0.000), LDLC (P=0.004), and VLDLC (P=0.026) over time. Conclusion: HC use is associated with significant increases in BMI, diastolic BP, TC, LDLC, and Castelli index I and II. These changes carry a potential risk in the development of CV disease. Keywords: oral, injectable, implant, cholesterol, body mass index